2019
DOI: 10.1016/j.heliyon.2019.e02455
|View full text |Cite
|
Sign up to set email alerts
|

A compact pulse-modulation cold air plasma jet for the inactivation of chronic wound bacteria: development and characterization

Abstract: A compact low-temperature plasma jet device was developed to use ambient air as plasma gas. The device was driven by a 2.52-kV high-voltage direct-current pulse in a burst mode, with a repetition rate of 2 kHz. The maximum plasma discharge current was 3.5 A, with an approximately 10 ns full-width half-maximum. Nitric oxide, hydroxyl radical, atomic oxygen, ozone, and hydrogen peroxide—important reactive oxygen and nitrogen species (RONS)—were mainly produced. The amount of plasma-generated RONS can be controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Therefore, treatment methods to enhance the bioactivity of the material surface should be employed. Air-plasma treatment enhances the surface properties of materials and has been utilized in agricultural production, waste management, as well as surface cleaning and disinfection (Petlin et al, 2017;Messerle et al, 2018;Saberi et al, 2018;Thana et al, 2019). The main advantages of this process are thin film deposition, increased wettability, induced cross-linking, and surface activation of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, treatment methods to enhance the bioactivity of the material surface should be employed. Air-plasma treatment enhances the surface properties of materials and has been utilized in agricultural production, waste management, as well as surface cleaning and disinfection (Petlin et al, 2017;Messerle et al, 2018;Saberi et al, 2018;Thana et al, 2019). The main advantages of this process are thin film deposition, increased wettability, induced cross-linking, and surface activation of the material.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Gram-negative bacteria are more sensitive than Gram-positive bacteria to CAP, a phenomenon likely to occur due differences in the cell wall thickness [ 5 ]. In agreement with our observation, Olatunde and co-workers [ 52 ] proposed the production of UV as one of the major factors in the mode of action in Gram-negative bacterial inactivation by CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma—regarded as the fourth state of matter—is a partially or completely ionised gas with unique chemical and physical properties which generates a wide range of highly reactive chemical agents when created in the ambient air. It has been increasingly studied due its antimicrobial, blood coagulation, wound healing and anti-tumour capability as well as in dentistry and several other biomedical applications [ 1 5 ]. The development of Cold Atmospheric Plasma (CAP) has brought advantages over widely used vacuum plasma technologies such as easier handling, inexpensive cost and straightforward design [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…COMPACT Air Plasma Jet, which is a coaxial kHz-driven pulsed plasma source, was used in this work. The details of the device are described elsewhere [ 14 ]. Briefly, the burst repetition rate (BRR), which is defined as an inverse of one pulse period, was set to 20 kHz and the pulse width was 5.0 μs.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Gas temperature of the plasma was estimated from a thermal equilibrium between a plasma-treated glass plate and the plasma plume as described in our previous work [ 14 ]. The plasma nozzle was perpendicularly set to the 22 mm × 22 mm × 0.16 mm glass plate with the gap distance of 5 mm.…”
Section: Experimental Methodsmentioning
confidence: 99%